Electroacupuncture Enhances Preproenkephalin mRNA Expression in Rostral Ventrolateral Medulla of Rats - Li, Min (2010)
Electroacupuncture (EA) causes prolonged suppression of reflex elevations in blood pressure for at least 60 minutes in anesthetized preparations. Thus, EA can modify sympathetic outflow and elevated blood pressure through actions in a number of hind brain regions, including the rostral ventrolateral medulla (rVLM). Since our previous data show that the opioid system plays a role in EA-related prolonged inhibition of presympathetic neuronal activity in the rVLM, we postulated that EA increases preproenkephalin (PPE) mRNA in this region, possibly for prolonged periods of time. Under α–chloralose anesthesia, rats received EA (1-2 mA, 2 Hz, 0.5 ms) at P5-P6 acupoints (overlying median nerves) or sham (needle placement without electrical stimulation) for 30 min. PPE mRNA in the rVLM also was evaluated in control rats that received surgery but no EA or sham treatment. 20 min, 1.5 h or 4 h following EA or sham treatment, PPE mRNA in the rVLM was analyzed by reverse transcription and quantitative real-time PCR. Relative ratios of PPE mRNA levels (normalized with 18s house keeping gene) were increased 1.5 h after EA stimulation (7.77 ± 1.39, n=6) relative to sham (2.84 ± 0.37, n=5) but were unchanged both 20 min and 4 h after EA, compared to the sham or surgery groups at the same time points. Thus, 30 min of EA transiently stimulates the production of enkephalin in a region of the brain that importantly regulates sympathetic outflow suggesting that even a single brief acupuncture treatment can increase the expression of this modulatory neuropeptide.